SOLAR REFRIGERATION SYSTEMS - A REVIEW - Puttewar, Amitkumar S.; Yawalkar, Roshan R.; Jiwtode, Vinay L.; Mohite, Gaurav R.; Anjikar, Akshay D. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
This paper gives the detailed review on solar operated refrigeration system. Now-a-days as theconventional sources are on the verge of depletion hence there is a necessity of renewable sources hat would help to run the electrical appliances. Conventional refrigeration systems consume lot of power and there is a need for energy conservation which is provided by means of solar refrigeration and also helps in minimizing the load on the electricity grid.